Shaping the future of conservation: a model for restoring oxbows in Iowa and beyond - Wilke, Karen; Rust, Andrew; Weissenfluh, Darrick; Iddings, Brandon; Wulf, Shane (Frontiers in Environmental Science, 2024)
Oxbows, once an abundant and natural feature of the landscape, have been nearly eliminated due to the effects of the Anthropocene, consequently impacting water quality, flood storage capacity, and the wildlife that depend on this habitat. These depressional basins within floodplains naturally accumulate sediment over time, but the sedimentation rate of oxbows over the last 100 years has greatly increased. The primary sources of sediment are from human activity, including erosion from agricultural fields and urban developments, drainage alterations, precipitation changes associated with climate change, and disconnection from their rivers and natural river hydraulics. Outlined in this manuscript is a step-by-step guide for restoring oxbows, based on 20 years of experience and lessons learned implementing oxbow restorations in Iowa on first-, second-, and third-order streams. Our goal is to provide conservation services providers and others interested in restoring degraded oxbows with the tools and expertise to confidently restore oxbows to achieve conservation goals.